Сокращаем на 7 получается 106/371, потом ещё на 53, и в итоге получаем: 2/7
91+48:(11-б)=99,б не равно 11
91 + 48/11-б =99
48/11-б =99-91
48/11-б =8
48=8(11-б)
6=11-б
б= 11-6
б= 5, б не равно 11
б=5
<span>5/3 (х-7) - 3х - 6 (х-8)/7= - (х +43/3)
</span>5(х-7) - 9х - 18 (х-8)/7= - 3х -43
5х-35 - 9х - 18 (х-8)/7= - 3х -43
<span>8-х = 18 (х-8)/7
</span><span>56-7х = 18 х-18*8
</span>56+<span>18*8 = 25 х
</span>200<span> = 25 х
х=8
</span>
А³+27в³=(а+3в)(а²-3ав+в²)=(а+3в)((а²+6ав+в²)-6ав-3ав)=
=(а+3в)((а²+6ав+в²)-9ав)=(а+3в)((а+3в)²-9ав)=
=(а+3в)³-9ав*(а+3в)
т.к. а+3в=2, то
(а+3в)³-9ав*(а+3в)=2³-9ав*2=8-18ав
что и требовалось доказать.